Existing and Potential Technologies for Carbon Emissions Reductions in the Indian Cement Industry : A Set of Technical Papers Produced for the Project 'Low Carbon Technology Road Map for the Indian Cement Industry' - World Bank (Washington, DC, 2013)
This set of technical papers was commissioned by the Cement Sustainability Initiative (CSI) members in India. CSI is a member-led program of the World Business Council for Sustainable Development (WBCSD). The report represents the independent work of the CII - Godrej Green Business Centre (CII, Godrej GBC), a center of excellence of Confederation of Indian Industry (CII) and the National Council for Cement and Building Materials (NCB). The author of each paper is shown after its title. It aims to identify, describe and evaluate technologies, which may contribute to increased energy efficiencies and reduced greenhouse gas emissions from cement production in India today and in the longer-term. The results have been reviewed by CII, NCB, CSI member companies and stakeholders like the International Energy Agency (IEA). All papers follow the same format, outlining the current status of the technology, the impact on energy consumption, anticipated benefits from implementation, the CO? reduction potential, main parameters influencing implementation, cost estimation, and the conditions, barriers and constraints of implementation. For the more futuristic technologies, where quantification is difficult, a qualitative summary is provided instead, indicating those technologies felt to be promising for future implementation and emissions reductions potential. In these papers, only the anticipated impact on energy consumption and barriers to further development can be shown. In every paper, a range of potential thermal and electrical savings is provided; this range has been reached through consultation with technical experts. Where INR costs are indicated, approximate USD equivalent costs have also been given, using exchange rate USD 1 = INR 50.